Fuzzy logic application for fault isolation of actuators - Bartyś, Michał; Kościelny, Jan M.; Rzepiejewski, Paweł (Computer Assisted Methods in Engineering and Science, 2022)
This paper is focused particularly on application of fuzzy logic approach for solving fault isolation problem of some class of industrial actuators described in the benchmark actuator definition [1]. Particular attention was paid for searching of applicable and acceptable solutions in terms of industrial implementations. The rational solution of the problem of setting fuzzy partitions for residual evaluation was proposed. The industrial benchmark study was applied for evaluating of proposed approach by means of the real process data acquired in normal and abnormal process states. The chosen examples of achieved results concerning fault isolability issues are presented.